Strength and Stiffness of Stabilized Alluvial Silt under Frost Actions - Haibo Wang; An Deng; Ping Yang (Advances in Materials Science and Engineering)
The Yellow River alluvial silt was stabilized into pavement base materials for cold regions. The stabilizing additives were cement, fly ash, and lime, which were included in a range of combinations and dosages when mixed with the silt. Freeze-thaw cyclic impacts were conducted on the treated samples to assess materials performance of withstanding the frost actions. The tests were conducted on samples cured for 7 days to up to 180 days. Test results show that the cement-fly ash-treated samples outperform the other two stabilization categories with respect to material strength and stiffness developed under both normal and frost conditions. Under the normal conditions, the material unconfined compressive (UC) strength rises to 3.0 MPa on day 28 depending on the cement and fly ash dosage used. If subjected to frost actions, the fly ash inclusions warrant a residual UC strength value of 1.3 MPa and above. The antifrost performance of the cement-fly ash-treated samples is related to thermal buffer capacity of the fly ash particles. Water adsorption and material soundness results agree with the strength and stiffness development. An optimal dosage was 3–6% for the cement and 0.3 for cement to fly ash mass ratio.